Innovative digital technologies to monitor and control pest and disease threats in Root, Tuber, and Banana (RT&B) cropping systems: progress and prospects - Kreuze, Jan F.; Adewopo, Julius; Selvaraj, Michael; Mwanzia, Leroy; Kumar, P. Lava; Cuéllar, Wilmer Jose; Legg, James P.; Hughes, D.P.; Blomme, Guy (Springer, 2022)
This chapter provides the first comprehensive review of digital tools and technologies available for the identification, monitoring, and control of pests and diseases, with an emphasis on root, tuber, and banana (RT&B) crops. These tools include systems based on identification keys, human and artificial intelligence-based identification based on smart applications, web interfaces, short messages services (SMS), or combinations thereof. We also present ideas on the use of image recognition from smartphones or unmanned aerial vehicles (UAVs) for pest and disease monitoring and data processing for modeling, predictions, and forecasting regarding climate change. These topics will be presented in the context of their current development and future potential but also the challenges, limitations, and innovative approaches taken to reach end users, particularly smallholder farmers, and achieve impacts at scale. Finally, the scope and limitation of private sector involvement demonstrates the need of publicly funded initiatives to maximize sharing of data and resources to ensure sustainability of unbiased advice to farmers through information and communication technology (ICT) systems.